Household consumption expenditures and the performance of provincial VAT revenue - Setiyaningsih, Widi Astuti Ari; Khoirunurrofik, Khoirunurrofik (Sebelas Maret Business Review, 2022)
This study examines the relationship between household consumption expenditures and the performance of VAT revenue at the provincial level in Indonesia during 2011-2019. Household consumption is divided into food and non-food contests. The PPN performance indicator is shown by the PPN C-efficiency ratio which is calculated from the VAT revenue for each province divided by the VAT rate multiplied by the Consumption GRDP. The results of the regression using the fixed-effect panel data estimation model show a positive and significant relationship between household consumption and VAT revenue in the province. This means that increasing aggregate household consumption, both food and non-food consumption, will increase the VAT-C efficiency ratio. The results also show that an increase in the consumer price index that is not followed by an increase in income will decrease VAT performance. Furthermore, the increase in the share of the tertiary sector as a direction of structural transformation will weaken the performance of VAT receipts. This is possible because the tertiary sector is still dominated by the service sector which is not subject to VAT and the trade sector in which there is a high level of informality.